Efficacy, Safety, and Clinical Outcomes of Splenorenal Shunt Surgery as a Therapeutic Intervention for Portal Hypertension Patients - Sembiring, Yan Efrata; Soebroto, Heroe; Puruhito, Ito; Winarno, Dhihintia Jiwangga Suta; Putra2, I Gusti Agung Made Adnyanya; Negoro, Sri Pramesthi Wisnu Bowo; Yasa, Ketut Putu; Dillon, Jeffrey Jeswant (Folia Medica Indonesiana, 2023)
Highlights: 1. This study systematically reviewed the efficacy, clinical outcomes, and safety of the splenorenal shunt procedure with a comprehensive and meticulous approach. 2. The splenorenal shunt procedure is an innovative surgical intervention that offers a viable option for the management of portal hypertension. Abstract Portal hypertension is the second most common gastrointestinal bleeding in cirrhosis and non-cirrhosis patients. The splenorenal shunt surgery is a potential intervention that may be considered for portal hypertension patients with clinical symptoms such as upper gastrointestinal bleeding caused by the rupture of gastro-esophageal varices. In this study, the researchers aimed to analyze the efficacy, clinical outcomes, and safety of splenorenal shunt surgery in portal hypertension patients. The sources were obtained from electronic search databases, including PubMed, Google Scholar, and ScienceDirect, using the keywords "Efficacy," "Safety," and "Clinical Outcomes." in relation to splenorenal shunt surgery in portal hypertension patients. The researchers set specific criteria for inclusion and exclusion to select the articles. This systematic review revealed the efficacy of the splenorenal shunt procedure with favorable outcomes. The success rate of splenorenal shunt surgery in reducing the clinical symptoms of portal hypertension varied between 66% and 100%. The prevailing complications observed in this study were shunt thrombosis, rebleeding, and thrombocytopenia. However, notable improvements could be achieved with general treatment. In terms of short- and long-term clinical outcomes, the splenorenal shunt procedure demonstrated favorable results. It can be concluded that splenorenal shunt surgery provides excellent clinical outcomes and should be considered a viable treatment option for patients with both cirrhotic and non-cirrhotic portal hypertension.